Designing connected marine reserves in the face of global warming. (22nd December 2017) - Álvarez‐Romero, Jorge G.; Munguía‐Vega, Adrián; Beger, Maria; del Mar Mancha‐Cisneros, Maria; Suárez‐Castillo, Alvin N.; Gurney, Georgina G.; Pressey, Robert L.; Gerber, Leah R.; Morzaria‐Luna, Hem Nalini; Reyes‐Bonilla, Héctor; Adams, Vanessa M.; Kolb, Melanie; et al.
Abstract: Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration (PLD) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLDs. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity. Abstract : Global warming can disrupt ecological connectivity among marine reserves by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the effectiveness of marine reserve networks, thus requiring adjusting their design to account for ocean warming. Using the Gulf of California as case study, we propose a framework for planning marine reserve networks that integrates graph theory and changes in larval connectivity due to ocean warming. Given expected changes in larval connectivity, we show that our graph‐theoretical approach based on centrality of habitat patches can help design better connected marine reserve networks for the future with equivalent costs.